(untitled) (Research, Society and Development, 2021)
Protected areas were created mainly for the conservation of biodiversity in the Amazon. However, there are high rates of deforestation within them, caused by the concession of roads, settlements and occupations. The use of geoprocessing techniques is of paramount importance to detect changes in land use and occupation. This study aims to model future scenarios in the Gurupi-MA Biological Reserve using the DYNAMIC EGO software, using the transition method to simulate deforestation trajectories until 2030, based on the variables: altitude, slope, roads, settlement and hydrographic area. As a result of the transition matrix, four transitions were computed: forest for deforestation, forest for illegal logging, illegal logging for deforestation and illegal logging. The forest-class areas showed the highest number of cells with changes, with a percentage of 0.25% deforestation and 6.08% of cells for illegal exploitation. It was found that several factors contribute to the increase in deforestation close to roads and settlements: illegal logging, cattle raising, hunting and human occupation, compromising the region’s fauna and flora. From the simulation of the future scenario (2030), it was observed that the class of deforestation tends to grow north of REBIO. By 2030, there may be a total reduction of 9.17% in forest cover in this UC. Through environmental modeling, together with the command, control and monitoring plans, it is possible to guide socioeconomic and environmental development in protected areas in the Amazon region of Maranhão, for the maintenance and protection of their natural wealth.